IMPLEMENTATION OF PANCASILA VALUES THROUGH SCHOOL CULTURE IN THE DIGITAL ERA AT KESATRIA PRIVATE MIDDLE SCHOOL MEDAN IN THE 2024 ACADEMIC YEAR - Zul Husna, Wan Annisa; Dharma , Surya (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2025)
The purpose of this study is to find out and describe how teachers implement humanitarian values in forming polite attitudes through PPKN learning. To find out and describe the supporting factors and inhibiting factors for teachers in implementing humanitarian values in forming polite attitudes through PPKn learning for class VII students of SMP Negeri 03 Solok Selatan. research object”. The informants in this study were the principal, vice principal for curriculum, PPKn subject teachers, BK teachers, students in grades VII D and VII E. The type of research used in this study was qualitative with descriptive methods. The implementation of humanitarian values in shaping students' politeness through PPKn learning in grade VII of SMP Negeri 03 Solok Selatan has been going well, by teaching the application of Pancasila values through PPKn learning, teacher role models, habituating politeness, collaboration with all school members, handling challenges and obstacles, as well as reflection and evaluation. So that politeness can be embedded in students well. There are several supporting and inhibiting factors in the implementation of humanitarian values in shaping students' politeness through PPKn learning in grade VII of SMP Negeri 03 Solok Selatan. The implementation of humanitarian values in shaping students' politeness through PPKn learning in grade VII of SMP Negeri 03 Solok Selatan is expected to have continuous implementation efforts so as to shape students' politeness better and there is good planning in implementing humanitarian values so that with good planning This can facilitate teachers and all related parties in implementing humanitarian values consistently, integratedly, and comprehensively.